The Offshore Services Value Chain : Developing Countries and the Crisis - Gereffi, Gary; Fernandez-Stark, Karina (2012)
This paper analyzes the recent evolution and impact of the global economic crisis on the offshore services industry. Using a global value chains framework, the authors classify the offshore services sector in a comprehensive set of general and industry-specific activities that correspond to different segments and stages in the value-adding process for services. Through an analysis of the impact of the economic crisis on the industry, a small decline in demand was found; however this did not cause any structural changes in the market. The crisis has created two opposing effects: general contraction of demand by existing customers due to the recession; and, at the same time, a substitution effect by which new services are being moved from developed countries to emerging economies in search of cost reduction. The paper concludes that the offshore services industry will continue to offer growth opportunities for developing countries not only among existing market players, but also a range of new countries. The industry has the potential to become an important source for employment and economic growth around the globe.